Freshwater access from a human rights perspective : a challenge to international water and human rights law - Bourquain, Knut (International studies in human rights ;, 2008)
Facing the deficits of international water law in safeguarding a basic water supply, the book discusses the appropriateness of a human rights-based approach to freshwater access, determines its legal basis in international human rights law, and develops suggestions for law improvement.